Characterization of SNARE proteins in human pituitary adenomas: targeted secretion inhibitors as a new strategy for the treatment of acromegaly? - Garcia, E; Trivellin, G; Aflorei, E; Powell, M; Grieve, J; Alusi, G; Pobereskin, L; Shariati, B; Cudlip, S; Roncaroli, F; Mendoza, N; Grossman, AB; et al. (2013)
CONTEXT: Targeted secretion inhibitors (TSIs), a new class of recombinant biotherapeutic proteins engineered from botulinum toxin, represent a novel approach for treating diseases with excess secretion. They inhibit hormone secretion from targeted cell types through cleavage of SNARE (soluble N-ethylmaleimide-sensitive factor-activating protein receptor) proteins. qGHRH-LH(N)/D is a TSI targeting pituitary somatotroph through binding to the GHRH-receptor and cleavage of the vesicle-associated membrane protein (VAMP) family of SNARE proteins. OBJECTIVE: Our objective was to study SNARE protein expression in pituitary adenomas and to inhibit GH secretion from somatotropinomas using qGHRH-LH(N)/D. DESIGN: We analyzed human pituitary adenoma analysis for SNARE expression and response to qGHRH-LH(N)/D treatment. SETTING: The study was conducted in University Hospitals. PATIENTS: We used pituitary adenoma samples from 25 acromegaly and 47 nonfunctioning pituitary adenoma patients. OUTCOME: Vesicle-SNARE (VAMP1-3), target-SNARE (syntaxin1, SNAP-23, and SNAP-25), and GHRH-receptor detection with RT-qPCR, immunocytochemistry, and immunoblotting. Assessment of TSI catalytic activity on VAMPs and release of GH from adenoma cells. RESULTS: SNARE proteins were variably expressed in pituitary samples. In vitro evidence using recombinant GFP-VAMP2and3 or pituitary adenoma lysates suggested sufficient catalytic activity of qGHRH-LH(N)/D to degrade VAMPs, but was unable to inhibit GH secretion in somatotropinoma cell cultures. CONCLUSIONS: SNARE proteins are present in human pituitary somatotroph adenomas that can be targeted by TSIs to inhibit GH secretion. qGHRH-LH(N)/D was unable to inhibit GH secretion from human somatotroph adenoma cells. Further studies are required to understand how the SNARE proteins drive GH secretion in human somatotrophs to allow the development of novel TSIs with a potential therapeutic benefit.